2015
DOI: 10.3390/v7052334
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cancer Cell Killing by the Adenovirus E4orf4 Protein

Abstract: During adenovirus (Ad) replication the Ad E4orf4 protein regulates progression from the early to the late phase of infection. However, when E4orf4 is expressed alone outside the context of the virus it induces a non-canonical mode of programmed cell death, which feeds into known cell death pathways such as apoptosis or necrosis, depending on the cell line tested. E4orf4-induced cell death has many interesting and unique features including a higher susceptibility of cancer cells to E4orf4-induced cell killing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 92 publications
(252 reference statements)
0
17
0
Order By: Relevance
“…It has been reported that when E4orf4 is expressed alone, it induces a unique mode of cancer-specific cell death [ 60 , 61 ]. Inhibition of the DDR may contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that when E4orf4 is expressed alone, it induces a unique mode of cancer-specific cell death [ 60 , 61 ]. Inhibition of the DDR may contribute to this process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E4orf4-induced cell death is more efficient in oncogene-transformed cells in tissue culture than in normal cells [ 60 ], indicating that study of E4orf4 signaling may have implications for cancer therapy. The basis for the cancer specificity of E4orf4-induced cell death will be better understood once knowledge of the underlying mechanisms is improved [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein phosphatase 2A (PP2A) is an important protein partner of E4orf4 which contributes to several E4orf4 functions, including attenuation of the DDR (26,39,(49)(50)(51)(52)(53). PP2A is a heterotrimeric enzyme containing a catalytic subunit (C), a scaffolding subunit (A), and one of several regulatory B subunits that belong to at least four unrelated gene families and which determine the specificity of the PP2A holoenzyme toward various substrates (54).…”
mentioning
confidence: 99%
“…However, there are no publications to suggest that ADP-mediated lysis might represent a necrotic process nor that ADP interacts with RIPK3 or MLKL. E4orf4, when expressed alone, can induce p53-independent, caspase-independent cell death 31 , 32 , but again, there is no evidence to support an interaction with any necrotic proteins, nor indeed to support a role for E4orf4 in cell death during productive adenovirus infection 33 .…”
Section: Discussionmentioning
confidence: 97%